2018
DOI: 10.4254/wjh.v10.i3.371
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics: From liver chiromancy to personalized precision medicine in advanced chronic liver disease

Abstract: Currently there is a lack of accurate biomarkers for diagnosis and prognosis in advanced liver diseases. Either the occurrence of first decompensation, or diagnosis of acute on chronic liver failure, severe alcoholic hepatitis, or hepatocellular carcinoma (HCC), none of the available biomarkers are satisfactory. Metabolomics is the newest of omics, being much closer than the others to the actual phenotype and pathologic changes that characterizes a certain condition. It deals with a much wider spectrum of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Regarding liver disease, it has been described that chronic hepatic disease itself alters fatty acid metabolism promoted by gut microbiota, 37 among others. Additionally, increased glycerol levels have been previously found in advanced chronic liver disease and hepatocellular carcinoma 38 . Thus, according to our results, cirrhotic HIV/HCV‐ and HCV‐infected patients showed a similar profile to that described for advanced cirrhosis of different aetiologies.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding liver disease, it has been described that chronic hepatic disease itself alters fatty acid metabolism promoted by gut microbiota, 37 among others. Additionally, increased glycerol levels have been previously found in advanced chronic liver disease and hepatocellular carcinoma 38 . Thus, according to our results, cirrhotic HIV/HCV‐ and HCV‐infected patients showed a similar profile to that described for advanced cirrhosis of different aetiologies.…”
Section: Discussionsupporting
confidence: 88%
“…As most of compounds pass through the liver after intestine absorption, this organ is a key regulator of many circulating metabolites, empowering the possibility to relate their serum levels to liver physiopathology. The small biocompounds (usually <1kDa molecules) profiles in chronic liver diseases including HCC have been investigated by NMR , but still there are no biomarkers able to predict time to recurrence after locoregional treatments that could be translated to clinical practice 89 .…”
Section: Uninvestigated Potential Biomarkersmentioning
confidence: 99%
“…Specifically, genetic polymorphisms identified in genome-wide association studies and novel proteins identified by proteomic technology offer the possibility of the further refinement and individualization of biomarkers of hepatic fibrosis [7]. Moreover, metabolomics, the identification and quantification of all or specified metabolites in a living system under a specific condition or disease [12,13,15], might be a powerful platform for discovering novel biomarkers and biochemical pathways to improve the diagnosis, prognostication and treatment of hepatic fibrosis [16]. The current review thus summarizes recent findings of metabolic alterations relevant to hepatic fibrosis from the aspects of individual pathways and systems biology, including transcriptomics, proteomics, and metabolomics in vitro, in animal models and in humans.…”
Section: Introductionmentioning
confidence: 99%